PENGARUH PENGGUNAAN TEPUNG LIMBAH KECAMBAH KACANG HIJAU TERHADAP BOBOT RELATIF DAN PANJANG ORGAN PENCERNAAN ITIK MAGELANG JANTAN - Fajar Wahyono, Santi Puspitasari Istna Mangisah (UPPM Politekik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2018)
This study aimed to determine the effect of mung bean sprouts waste on relative weight and length of digestive organs in male magelang ducks. The material used 120 male Magelang duck 4 weeks old with an average initial weight of 930,66 ± 136,29 g. The research used Randomized Block Design (RBD) with 4 treatments and 4 replication. The treatments were levels of mung bean sprouts waste 0, 5, 10 and 15%. Parameters measured were relative weight and length of digestive organs in male Megelang duck. Data were analyzed by analysis of variance, when the effect of treatment was significant, it was continued by Duncan Multiple Range Test (DMRT). The results showed that use of mung bean sprouts significantly (P<0,05) on relative weight ventriculus, but there were nosignificant on relative weigh of other organs and length of digestive organs in male Magelang duck. In conclusion, the use mung bean sprouts waste increase relative weight ventriculus the highest on level 5% (T1) was 2,15%, but was not able to increase the relative weight and length of other digestive organs in male Magelang duck.Keywords: male Magelang duck, mung bean sprouts waste, digestive organs